The Code of City of Birmingham, Alabama 662 (1917) - (:unkn) unknown (General Publisher, 1917)
Prohibited carrying fire arms, throwing stones, or other missiles in any public parks
--
Keywords: CARRY - CERTAIN PUBLIC PLACES